A ANALISIS POLA SEBARAN SPBU DI KOTA DENPASAR - Suciptawati, Ni Luh Putu; Dipa, I Putu Gede Prada; Pradantya Putra, Nyoman Gede Mas (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2023)
The existence of public fuel filling stations (SPBU) is crucial in big cities so that vehicle mobility in the city can run smoothly. Denpasar City with an area of ​​127.78 km2 consisting of four sub-districts has 49 gas stations. Until now, the distribution pattern of gas stations in the city of Denpasar is not yet known. This study aims to determine the pattern of distribution of gas stations in Denpasar city. To obtain data, the distance between one gas stations and the nearest gas stations are measured using GPS. By using the nearest neighbor method, it is found that the distribution pattern of gas stations in Denpasar city are random. The random distribution pattern shows that all sub-districts in Denpasar city have gas stations but not evenly distributed. With this result, it is hoped that if anyone wants to build a gas station, it is advisable to build it in an area where there is no gas station close by